Research progress on high-concentration oxygen therapy after cerebral hemorrhage - Zeng, He; Zeng, Dakai; Yin, Xiaoping; Zhang, Wumiao; Wu, Moxin; Chen, Zhiying (Frontiers in Neurology, 2024)
Recently, the role of high-concentration oxygen therapy in cerebral hemorrhage has been extensively discussed. This review describes the research progress in high-concentration oxygen therapy after cerebral hemorrhage. High-concentration oxygen therapy can be classified into two treatment methods: hyperbaric and normobaric high-concentration oxygen therapy. Several studies have reported that high-concentration oxygen therapy uses the pathological mechanisms of secondary ischemia and hypoxia after cerebral hemorrhage as an entry point to improve cerebral oxygenation, metabolic rate, cerebral edema, intracranial pressure, and oxidative stress. We also elucidate the mechanisms by which molecules such as Hypoxia-inducible factor 1-alpha (HIF-1α), vascular endothelial growth factor, and erythropoietin (EPO) may play a role in oxygen therapy. Although people are concerned about the toxicity of hyperoxia, combined with relevant literature, the evidence discussed in this article suggests that as long as the duration, concentration, pressure, and treatment interval of patients with cerebral hemorrhage are properly understood and oxygen is administered within the treatment window, it can be effective to avoid hyperoxic oxygen toxicity. Combined with the latest research, we believe that high-concentration oxygen therapy plays an important positive role in injuries and outcomes after cerebral hemorrhage, and we recommend expanding the use of normal-pressure high-concentration oxygen therapy for cerebral hemorrhage.